Mathematics in Collaboration with Science - Joshi, Hemali P. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Here, some topics in collaboration with Mathematics have been chosen. The topics were thoroughly studied in a creative way. Chemistry has concepts like atomic number, atomic mass, Valency, etc. These concepts have mathematical numbers to be taken into consideration. Also, the number of electrons in an atom play an important role in the formation of Chemical Formula. The creative and fun-filled games were constructed to make the concept learning more feasible. A strong connection of Mathematics with Biology was also discovered. Fibonacci series and numbers were seen to be included in living organisms as well. The venation patterns of some random Dicotyledonous and Monocotyledonous plants were studied and the connection of Fibonacci numbers with venation was discovered. Also, the concept of Symmetry was also studied under the domain of Biology. In order to study the above-mentioned concepts, Motley Method was used. Motley Method basically means different components brought together in a frame to understand the concepts easily.